pendampingan pendampingan pemanfaatan GC di SMP Ma'arif 1 Ponorogo: Pendampingan Melalui Google Classroom Hasil Pendampingan Melalui Google Classroom Pemanfaatan Pendampingan Pembelajaran Google Classroom - sabtian rengga febriansyah (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The COVID-19 pandemic has prompted significant changes in the education system, from face-to-face learning to online learning. This article discusses assistance in using Google Classroom as a solution to support the teaching and learning process at SMP Ma'arif 1 Ponorogo. Descriptive qualitative methods were used to describe experiences and challenges during mentoring. The research results show that Google Classroom increases the efficiency of managing assignments and materials, improves communication between teachers and students, and provides flexibility in time and place in learning. However, obstacles such as internet network disruptions and students' limited technological competence are challenges that must be overcome. This article recommends intensive training for teachers and students to maximize the potential of online learning using Google Classroom.